Transformasi Sumber Daya Manusia Terhadap Penanganan Muatan Berbahaya pada Kapal Dobonsolo Sesuai IMDG Code PM 16 Tahun 2021 di PT Pelayaran Nasional Indonesia Cabang Jayapura - Wening Nalurita; Noviana Puspitasari (Port Management and Maritime Administration Journal, 2025)
The purpose of this study is to find out the basic things that cause organizational change, to find out the development of the quality of human resources that are carried out, the lack of mastery in handling hazardous cargo. The study uses a qualitative approach with a descriptive method. Data was taken using interview techniques, observation, documentation. The informants used in the study were Experts. The data that has been collected is then subjected to data reduction, data presentation, and verification. The results of the study are the things that underlie organizational change to maintain the company's excellence by making organizational changes in accordance with the IMDG Code PM 16 of 2021, making changes to the quality of human resources who have expertise in accordance with the provisions in force in various sectors with the implementation of upskilling and reskilling, handling of hazardous cargo carried out in accordance with applicable procedures to obtain efficiency and work safety that is more guaranteed, handling of hazardous cargo has been carried out in accordance with the IMDG Code PM 16 of 2021 in accordance with the latest regulations with good cooperation so that in loading it can arrive at its destination safely.